(untitled) (Research, Society and Development, 2020)
Background of this study is the internet technology improvement through social media Instagram which has huge potential on online selling. It found the fraud case that occurs through Instagram it is causes purchasing decreases. Price, information quality and purchase interest as the main factors which causes someone to shopping via online. The research cases study implementing to an online shop which is engaged in the food sector. This research used 5 variables such as consumer trust, price, information quality as an independent variable, online purchasing decisions as a dependent variable, with purchasing interest as variable intervening. This research used SmartPLS 3.0. The research method that used is qualitative approach, the associative type research, data collection technique used questionnaire, and the type of data that used is primary data which obtained of 95 respondents which already shopping via online in Instagram. The result showed that consumer trust, price, and information quality on purchasing interest with consumer trust and purchasing interest on the purchasing decision which has positive effect and significant, while price and information quality has no effect on the purchasing decision. Purchase interest is able to mediate between consumer confidence in purchasing decisions, the price of the purchase decision, and the intention of buying is not able to mediate the quality of the information on the purchase decision.